Harm from Known Others' Drinking by Relationship Proximity to the Harmful Drinker and Gender: A Meta-Analysis Across 10 Countries - Stanesby, O.; Callinan, S.; Graham, K.; Wilson, I.; Greenfield, T.; Wilsnack, S.; Hettige, S.; Hanh, H.; Siengsounthone, L.; Waleewong, O.; Laslett, Anne-Marie (Wiley-Blackwell Publishing, Inc., 2018)
© 2018 by the Research Society on Alcoholism Background: Drinking is a common activity with friends or at home but is associated with harms within both close and extended relationships. This study investigates associations between having a close proximity relationship with a harmful drinker and likelihood of experiencing harms from known others' drinking for men and women in 10 countries. Methods: Data about alcohol's harms to others from national/regional surveys from 10 countries were used. Gender-stratified random-effects meta-analysis compared the likelihood of experiencing each, and at least 1, of 7 types of alcohol-related harm in the last 12 months, between those who identified someone in close proximity to them (a partner, family member, or household member) and those who identified someone from an extended relationship as the most harmful drinker (MHD) in their life in the last 12 months. Results: Women were most likely to report a close male MHD, while men were most likely to report an extended male MHD. Relatedly, women with a close MHD were more likely than women with an extended MHD to report each type of harm, and 1 or more harms, from others' drinking. For men, having a close MHD was associated with increased odds of reporting some but not all types of harm from others' drinking and was not associated with increased odds of experiencing 1 or more harms. Conclusions: The experience of harm attributable to the drinking of others differs by gender. For preventing harm to women, the primary focus should be on heavy or harmful drinkers in close proximity relationships; for preventing harm to men, a broader approach is needed. This and further work investigating the dynamics among gender, victim–perpetrator relationships, alcohol, and harm to others will help to develop interventions to reduce alcohol-related harm to others which are specific to the contexts within which harms occur.